Manajemen Pendidikan Islam Berbasis Keadilan: Studi atas Hadits ke-24 Arba'in An-Nawawi tentang Larangan Kezaliman - Jubaedi, Ahmad; Bachtiar, Machdum; asyiah, Euis (Jurnal Ilmiah Wahana Pendidikan, 2024)
Justice is a fundamental principle in Islam and is critically important in educational management. This study aims to analyze the concept of justice in the 24th Hadith of Arba'in An-Nawawi and explore its implementation in contemporary Islamic educational management. The research employs a qualitative library approach, integrating textual hadith analysis with contextualization in modern Islamic educational management. Primary data sources include the Arba'in An-Nawawi collection and its commentaries, while secondary sources encompass Islamic educational management literature. The research reveals three dimensions of justice: accessibility, processual, and outcome-based. It formulates four practical implementation models: inclusive planning, participatory organization, transformative leadership, and transparent control. Findings demonstrate that justice implementation requires a structural and cultural transformation in Islamic educational systems, encompassing policy reform, recruitment systems, learning methods, and evaluation mechanisms. The study contributes to developing a holistic, inclusive, and empowering Islamic educational management approach.